ALKOHOL I GRØNLAND: Problemorienteret forskning og lokal drikkekultur - Sørensen, Bo Wagner (Tidsskriftet Antropologi, 1998)
Bo Wagner Sørensen: Alcohol in Greenland: Problem-oriented Research and Local Drinking Culture The article sums up the main literature on alcohol in Greenland, showing its markedly problem-oriented approach. Drinking in general is read as a sign of the time - i.e., as a symptom that something has gone wrong in Greenlandic society. More specifically, the literature seems informed by the idea that Greenlanders are a people in transition, that they are trapped in between the so-called traditional society and a modem lifestyle and as such ridden by “acculturative stress”. Alcohol, according to this perspective, may have a function of reducing anxiety. Interestingly, the explanatory framework is roughly the same in research dating back to the early 1960s as in the recent research from the late 1990s, even if Greenland has changed in important ways during this time spån. In contrast to the general approach, I focus empirically on male drinking sessions, showing how they centre around beer drinking, and sometimes on getting drunk. The men involved are motivated, however, not primarily by the beer itself, but by the sense of community created during the sessions. The drinking sessions are not unproblematic as they may conflict with family obligations, and they also seem to confirm the idea underlying the dominant discourse on gender that men, in contrast to their female counterparts, are irresponsible, immature and even problem-ridden. The overall aim of the article is to point to new ways of going about alcohol research in Greenland in order to counter a one-sided problem-oriented approach that focuses on social anomie.